Prevalence, knowledge, and treatment of transient ischemic attacks in China - Wang, Yilong (Neurology, 2015)
OBJECTIVES: To investigate the prevalence, knowledge, and treatment of TIA in a Chinese adult population. METHODS: We conducted a complex, multistage, probability sampling–designed, cross-sectional, nationwide survey of 98,658 Chinese adults in 2010. Possible TIA cases were first identified by symptoms recall or self-reported history of TIA through face-to-face interviews, and the final diagnosis was then made by expert neurologists through phone interviews or record review. RESULTS: The age-standardized prevalence of TIA was 2.27%. Clinically, only 16.0% of the participants were diagnosed before the study. The prevalence of TIA was higher in women and in patients who were older, had less education, were current smokers, lived in rural or undeveloped areas, and had a history of stroke, hypertension, myocardial infarction, dyslipidemia, or diabetes. Based on the survey responses, approximately 3.08% of Chinese adults had knowledge of TIA. Among patients with TIA, only 5.02% received treatment and 4.07% received guideline-recommended therapy. CONCLUSIONS: TIA is prevalent and an estimated 23.9 million people in China may have experienced a TIA. Public knowledge on TIA is very limited. TIA appears to be largely undiagnosed and untreated in China. There is an urgent need to develop strategies to improve the identification and appropriate management of TIA.